Photophysicochemical studies of phenylthio phthalocyanines interaction with gold nanoparticles and applications in dye sensitised solar cells and optical limiting - Forteath, Shaun (Rhodes University, Faculty of Science, Department of Chemistry, 2012)
The syntheses, spectroscopic characterisation, photophysical and photochemical studies have been conducted for a variety of phenylthio substituted phthalocyanines (Pcs). Comparisons have been made taking into consideration the influence of the central metal ion, solvent properties and substituent type. The optical limiting properties were also determined for all the Pcs synthesised. A low-symmetry metallophthalocyanine complex was similarly characterised and the photoelectrochemical parameters determined when used as a sensitiser of nanoporous ZnO. The symmetric analogue was conjugated to gold nanoparticles to determine the influence of interactions on its photophysical properties and distinct differences occurred in the absorption and fluorescence spectra suggesting successful formation of conjugates.
Keywords: Phthalocyanines; Nanoparticles; Photochemistry